Three Novel Cases of Trilateral Retinoblastoma: An Approach towards Genetic Diagnosis - Renata Mendes de Freitas (Recent Research Advances in Biology Vol. 10, 2021)
The trilateral retinoblastoma is the heritable form of retinoblastoma associated with an intracranial tumor that most effect the pineal gland, as well as the suprasellar or intrasellar region of the brain. Because of this rarity, few works on the molecular genetics of this tumor has been reported being important the report of these cases associated with molecular studies. This work aims to alert health professionals to the early diagnosis of retinoblastoma, and to highlight the use of intracranial magnetic resonance imaging to track secondary tumors, including trilateral retinoblastoma. More than 50% of trilateral retinoblastoma is diagnosed at the time of retinoblastoma diagnosis by magnetic resonance imaging, suggesting that baseline screening for trilateral retinoblastoma might indeed be useful. In this paper, we present three cases of trilateral retinoblastoma with diagnosis obtained by magnetic resonance imaging and the molecular data found for each proband.